THE EFFECT OF GIVING HOMEWORK SUCH AS CONCEPT MAPPING OF COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) LEARNING MODEL ON STUDENTS’ BIOLOGY ACHIEVEMENT AT THE X GRADE STUDENTS OF SMA GUNUNG TALANG KABUPATEN SOLOK - Itgo Hatchi (Institut Pendidikan Tapanuli Selatan, 2016)
The learning process of Biology in SMA Negeri 2 Gunung Talang focus on teacher, as the consequence the students’ biology achievement is still low. There are many efforts which teacher can do to motivat students in learning process to get better result such as by giving concept mapping of Cooperative Reading Integrated and Composition (CIRC). This research is aimed to know the effect of using concept mapping of Cooperative Reading Integrated and Composition (CIRC) learning model on students’ biology achievement at the X grade students of SMA Negeri 2 Gunung Talang Kabupaten Solok. The kind of this research is experimental research where the population is all X grade students of SMA Negeri 2 Gunung Talang Kabupaten Solok in 2010/2011 academic year that consist of 4 classes. The sample is X3 as experimental class and X4 as control class, they are taken by random sampling technique. The design used is randomized control-group postest only design. The instrument used is a group of achievement test at the end of this research. The technique of analyzing data by using U test if Ucalculation ˃ Utable, so the hypothesis (H1) is accepted and H0 is rejected. From the research findings, Ucalculation is 255 and Utable is 216, so Ucalculation ˃ Utable, it means the hypothesis H1 is accepted and H0 is rejeced. It can be concluded that there is a positive effect of giving homework such as concept mapping of Cooperative Integrated Reading and Composition (CIRC) learning model on students’ biology achievement at the X grade students of SMA Negeri 2 Gunung Talang Kabupaten Solok.